The Mesolithic-Neolithic transition in Ukraine : new radiocarbon determinations for the cemeteries of the Dnieper Rapids Region - Lillie, Malcolm C.
Large Mesolithic and Neolithic cemeteries that span the Mesolithic-Neolithic transition are scarce in Europe. As such, understanding the Mesolithic-Neolithic transition is rarely easy when using the direct evidence from carbon-dating of human remains. A new dating programme for the Ukrainian cemeteries of the Dnieper Rapids region throws up considerable discrepancies between typological seriation as a means to assign burials to the Mesolithic or to the Neolithic and the carbon evidence.